Diversity and Distribution of Morinda Species in Andaman Islands - Singh, D. R.; Srivastava, R. C. (Indian Forester, 2011)
Andaman and Nicobar Islands being close to the equator, enjoy tropical humid climate condition, which are much congenial for vegetative and reproductive growth of Morinda citrifolia. Eighty species of Morinda have been reported globally of which, twelve species from different parts of India and three known species found to be in Andaman and Nicobar Islands. Great variability within the species is the common occurrence. Owing to its high nutritive value, medicinal importance and having national and international market, there is a possibility for emerging as one of the most remunerative fruit crop to the island farmers. It flowers and fruiting occurs round the year. Noni plant is distributed in almost all parts of the island. It can be found near the coast, in open lands, and grass lands, in gluches and distributed forest of the dryer areas. It tolerates high soil salinity and brackish water stagnation, therefore, the Morinda citrifolia, is the best choice for planting in these affected lands. Farmers are showing much interest in Noni cultivation because of assured income from this plantation. Therefore, studies on its diversity have to be critically examined for various uses from the different tropical parts of the country.